2022
DOI: 10.1007/s13659-022-00331-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural derivatization strategies of natural phenols by semi-synthesis and total-synthesis

Abstract: Structural derivatization of natural products has been a continuing and irreplaceable source of novel drug leads. Natural phenols are a broad category of natural products with wide pharmacological activity and have offered plenty of clinical drugs. However, the structural complexity and wide variety of natural phenols leads to the difficulty of structural derivatization. Skeleton analysis indicated most types of natural phenols can be structured by the combination and extension of three common fragments contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 211 publications
(226 reference statements)
0
5
0
Order By: Relevance
“…Phenols and polyphenols are nucleophiles susceptible to electrophilic substitution reactions due to their high electron density [36]. The phenolic OH group facilitates the effective delocalization of the charge in the aromatic ring through resonance.…”
Section: Oxidation Of Polyphenolic Compounds To Quinonesmentioning
confidence: 99%
“…Phenols and polyphenols are nucleophiles susceptible to electrophilic substitution reactions due to their high electron density [36]. The phenolic OH group facilitates the effective delocalization of the charge in the aromatic ring through resonance.…”
Section: Oxidation Of Polyphenolic Compounds To Quinonesmentioning
confidence: 99%
“…Consistent with our findings, most of these compounds were suggested to interfere with the early stages of the viral replication cycle (in adsorption, penetration, and RNA replication), except matrine, which was shown to regulate host immune response (in vivo). Since highly efficacious natural compounds are extremely difficult to discover, structural modification and derivative synthesis may be considered to enhance their efficacy (Lin et al, 2022;Xu et al, 2022). Furthermore, Shang, Xu, and Yin (2013) reported that 6-amino acid peptide (LVLQTM) was capable of binding the active site and inhibiting 2A protease (Falah et al, 2012), metrifudil and N6-benzyladenosine inhibited 2C helicase (Arita et al, 2008), and rupintrivir inhibited 3C protease ( Kuo et al, 2008;Cui et al, 2011;Tan et al, 2016).…”
Section: Virucidal Efficacy Suspension Testmentioning
confidence: 99%
“…A single uncharacterized example of a monocyclic B–OH containing diazaborine was reported as a bioconjugate linker in a DNA-encoded library, while the related 1,2-azaborine has remained unreported . In light of the vast occurrence of phenol-containing substructures in biologically active natural and synthetic compounds, , the preparation of boranol-containing oxaza- and diazaborines has significant implications in bioisosterism and drug discovery. This sort of novel chemotype may show unique properties amenable to engineering gain-of-function through additional H-bonding and reversible covalent exchange with the pseudophenolic boranol unit.…”
Section: Introductionmentioning
confidence: 99%